2013
DOI: 10.1186/2047-2994-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Clostridium difficile infection in Asia

Abstract: While Clostridium difficile infection (CDI) has come to prominence as major epidemics have occurred in North America and Europe over the recent decade, awareness and surveillance of CDI in Asia have remained poor. Limited studies performed throughout Asia indicate that CDI is also a significant nosocomial pathogen in this region, but the true prevalence of CDI remains unknown. A lack of regulated antibiotic use in many Asian countries suggests that the prevalence of CDI may be comparatively high. Molecular stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
184
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 63 publications
(110 reference statements)
14
184
1
2
Order By: Relevance
“…Therefore, we consider that the 50 clinical isolates do not belong to PCR ribotypes 001, 027 or 078, which have recently become globally widespread. Because PCR ribotypes 001, 027 and 078 have not spread to Japan to date (Collins et al, 2013), our results seem reasonable.…”
Section: Reproducibility In Identification Of Clostridium Difficile Asupporting
confidence: 50%
“…Therefore, we consider that the 50 clinical isolates do not belong to PCR ribotypes 001, 027 or 078, which have recently become globally widespread. Because PCR ribotypes 001, 027 and 078 have not spread to Japan to date (Collins et al, 2013), our results seem reasonable.…”
Section: Reproducibility In Identification Of Clostridium Difficile Asupporting
confidence: 50%
“…The results obtained showed that iron fortification in infants adversely affected the gut microbiota, with an increase in the proportion of some pathogenic bacteria, including Escherichia coli, Salmonella, Clostridium perfringens and C. difficile [60]. A review [61] on the epidemiology of C. difficile in Asia shows that infection occurred at similar rates to other areas but with a predominance of variant toxin A and toxin B positive strains, including PCR-ribotypes 017 and 018. In contrast with the situation in America and Europe, PCR-ribotypes 027 and 078 have rarely been reported in Asia.…”
Section: Difficile Outside Europe and North Americamentioning
confidence: 90%
“…In contrast with the situation in America and Europe, PCR-ribotypes 027 and 078 have rarely been reported in Asia. The unregulated use of antibiotics in some Asian regions and the lack of surveillance raise concerns over the risk of bacterial mutation and infection [61]. An additional review describes the situation in Thailand in detail.…”
Section: Difficile Outside Europe and North Americamentioning
confidence: 99%
“…Estimates regarding the occurrence of C. difficile infection (CDI) in United States per year has been mentioned in a study [3]. A few reports are available regarding the prevalence of CDI in Asian countries [4,5]. The mutant hypervirulent strain, NAP1/BI/027 (North American Pulse-field gel electrophoresis type 1 /restriction endonuclease analysis BI/ribotype 027) which was responsible for the outbreaks of CDAD in many parts of the world has given due significance to the organism [6].…”
Section: Introductionmentioning
confidence: 99%